Impact of the economic crisis on human mobility in Japan : a preliminary note - Yoshitaka Ishikawa (Belgeo)
The central aim of this paper is to explore the impact of the global economic crisis on different categories of human mobility, including migration and tourism, in Japan. The major findings can be summarized as follows. First, since the fall of 2008 the crisis has had a far-reaching influence on Japan, for both the ethnic majority and minorities. Second, the intensity of the negative impact has varied by metropolitan areas and nationalities. Japanese nationals in the Tokyo metropolitan area and migrant workers (particularly Brazilians) in the Nagoya metropolitan area and central Japan manufacturing prefectures are the most affected population groups. Finally, support programs by the Japanese government were problematic, and, in particular, the program that provided incentives for migrant workers to voluntarily return to their home countries was introduced too late. However, it is too early to clearly elucidate the full impact of the crisis, since the latest available data confirm that the current situation remains in a state of crisis.